2021
DOI: 10.1007/s11357-021-00379-1
|View full text |Cite
|
Sign up to set email alerts
|

Prefrontal cortex activation during dual-task walking in older adults is moderated by thickness of several cortical regions

Abstract: healthy community-dwelling older adults, whose cortical thickness was measured via MRI. HbO 2 levels in the PFC, measured via fNIRS, were assessed during active walking under STW and DTW conditions. Statistical analyses were adjusted for demographics and behavioral performance. Linear mixed-effects models revealed that the increase in HbO 2 from STW to DTW was moderated by cortical thickness in several regions. Specifically, thinner cortex in specific regions of the frontal, parietal, temporal, and occipital l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 104 publications
2
33
0
Order By: Relevance
“…This also results in a stronger relationship between temporal lobe structure and dual task walking, which only emerges in older age when these neural resources start to become limited. This interpretation fits with a recent report of an association between lower cortical thickness and greater increases in prefrontal oxygenation from single to dual task walking, with no effect on performance (Ross et al, 2021 ). The study authors suggested that older adults with the poorest neural resources (i.e., the thinnest cortex) also required the most compensation from alternative brain regions (i.e., the greatest increases in prefrontal oxygenation) to maintain performance.…”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…This also results in a stronger relationship between temporal lobe structure and dual task walking, which only emerges in older age when these neural resources start to become limited. This interpretation fits with a recent report of an association between lower cortical thickness and greater increases in prefrontal oxygenation from single to dual task walking, with no effect on performance (Ross et al, 2021 ). The study authors suggested that older adults with the poorest neural resources (i.e., the thinnest cortex) also required the most compensation from alternative brain regions (i.e., the greatest increases in prefrontal oxygenation) to maintain performance.…”
Section: Discussionsupporting
confidence: 92%
“…We did not identify any statistically significant age group differences in the relationship between the DTcost of gait speed or variability and regional gray matter volume. While extensive previous literature has examined relationships of single task overground walking with gray matter and cerebellar volume (e.g., Rosano et al, 2007 ; Dumurgier et al, 2012 ; Callisaya et al, 2013 ; Beauchet et al, 2015 ; Demnitz et al, 2017 ), comparatively less work has examined such relationships with dual task walking (Allali et al, 2019 ; Lucas et al, 2019 ; Tripathi et al, 2019 ; Wagshul et al, 2019 ; Ross et al, 2021 ). Further, these studies had methodological differences from our work (e.g., they used an alphabet task instead of serial 7s as the cognitive task).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations